Fragmented time and domiciliary care quality. Issue 1 (6th January 2020) - Atkinson, Carol; Crozier, Sarah
Abstract : Purpose: The purpose of this paper is to examine the marketization of domiciliary care, its consequences for employment practice, specifically fragmented time, and the implications for care quality. Design/methodology/approach: Focus groups and face-to-face or telephone interviews were conducted with care commissioners, service providers and care workers across Wales. There were 113 participants in total. Findings: These demonstrate fragmented time's negative consequences for service providers, care workers and, ultimately, care quality. Research limitations/implications: No care recipients were interviewed and care quality was explored through the perceptions of other stakeholders. Social implications: For policy makers, tensions are evidenced between aspirations for high-quality care and commissioning practice that mitigates against it. Current care commissioning practices need urgent review. Originality/value: The research extends the definition of fragmented time and integrates with a model of care quality to demonstrate its negative consequences. Links between employment practice and care quality have only previously been hinted at.